Charulata - Ray, Satyajit 1921-1992 (The Criterion collection, 2013)
"Satyajit Ray's exquisite story of a woman's artistic and romantic yearning takes place in late nineteenth-century, pre-independence India, in the gracious home of a liberal-minded, workaholic newspaper editor and his lonely wife, Charulata (Madhabi Mukherjee). When her husband/s poet cousin (Soumitra Chatterjee) comes to stay with them, Charulata finds herself both creatively inspired and dangerously drawn to him. Based on a novella by the great Rabindranath Tagore, Charulata is a work of subtle textures, a delicate tale of a marriage in jeopardy and a woman taking the first steps toward establishing her own voice." [criterion.com]